2011
DOI: 10.1111/j.1468-1331.2011.03540.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain in amyotrophic lateral sclerosis: a population‐based controlled study

Abstract: Our study indicates that pain is frequent in all stages of ALS, but that it often goes underrecognized and undertreated. It is significantly more frequent in patients with ALS than in population-based controls. Future studies need to clarify the mechanisms of pain in ALS and determine the most effective treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
107
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 23 publications
(36 reference statements)
12
107
2
Order By: Relevance
“…Pain in our series was, on average, moderate in intensity, but was severe in some patients, and a barrier to daily life activities. Similar findings have been observed by others (2,3,6) and by us in a previous series of patients recruited by a different method (23). Importantly, relief as a result of pain treatments was not impressive, averaging less than 50% (100% ¼ complete relief).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Pain in our series was, on average, moderate in intensity, but was severe in some patients, and a barrier to daily life activities. Similar findings have been observed by others (2,3,6) and by us in a previous series of patients recruited by a different method (23). Importantly, relief as a result of pain treatments was not impressive, averaging less than 50% (100% ¼ complete relief).…”
Section: Discussionsupporting
confidence: 74%
“…Nearly a quarter of the sample experienced no pain relief, and this is a major concern. Others have found that the use of opioids is common, yet those same series demonstrate significant average pain (2,3,6). It is unknown whether the poor pain control is due to lack of adequate assessment of pain by the health care team, ineffective treatments, or other causes, but it certainly is meaningful that almost 30% of our study patients were not receiving any treatment for their pain.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The most often reported locations are the upper and lower extremities, shoulders, and hips 9 . Odynophagia is perceived as pain evoked during swallowing 10 .…”
mentioning
confidence: 99%
“…11 However, many articles pointed out that pain in ALS or MND has under-recognized and underestimated. 12,13 This study focused on end-of-life care involving the use of NIV. The aim of this study was to clarify the aspects of pain experienced by patients with ALS receiving NIV at end-of-life.…”
Section: Introductionmentioning
confidence: 99%